Implementation And Approach On The Oxidation Of Halogenated Fluorenes By Permanganate In Alkaline Medium With Innovative Mechanism - Dr. Ramesh Kumar N . Patel (International Journal of Advanced Science and Technology, 2020)
The oxidation kinetics of fluorene (Fl) and its halogenated derivatives, specifically, 2,7- dichlorofluorene (Fl-Cl), 2,7- dibromofluorene (Fl-Br) and 2,7-diiodofluorene (Fl-I), using potassium permanganate in alkaline medium has been studied spectrophotometrically at a constant ionic energy of zero.1 mol dm-three and at 25°C. A first order kinetics has been located in these reactions with respect to [permanganate]. Fractional-first order dependences of the reactions at the [reductants] and [alkali] were found out. No great effect on the response costs with the aid of increasing ionic energy changed into recorded. Intervention of loose radicals was discovered in the reactions. The reactions mechanism describing the kinetic effects has been proposed which entails formation of 1:1 intermediate complexes between fluorene derivatives and the energetic species of permanganate. Keywords: Permanganate, Oxidation, Fluorenes, Kinetics, Mechanism.